THE QUO VADIS OF BANCKRUPTY SETTLEMENT AND PKPU LAWS ON SHARIA BANKING - Firman Wahyudi (Jurnal Hukum dan Peradilan, 2019)
Normatively, based on the decision of the Constitutional Court No. 93/PUU/X/2012 the settlement of Islamic economic disputes becomes the absolute competence of the Religious Courts. However, at the empirical level, there are still sharia economic disputes which are still decided by the Commercial Court (general), namely bankruptcy cases and PKPU on the sharia bank. This paper focuses on three things, first, what causes these cases to remain under the authority of the Commercial Court, secondly, what are the legal consequences if the case is resolved through the Commercial Court and how the legal arguments about the competence of the Religious Courts in bankruptcy cases and PKPU on sharia bank. This research method is normative law by examining a set of legal materials related to bankruptcy and PKPU. The analysis used is synchronization of the norms of Law No. 37 of 2008 and PERMA No. 2 of 2008. The results of the study found that the cause of the case is still handled by the Commercial Court because of a conflict of norms between the Bankruptcy Act and PERMA regarding KHES which still has not been finalized, the conditions legal vacuum regarding bankruptcy based on the sharia contract and the existence of the KMA letter regarding the instruction for the implementation of book II. Legal consequences if the case is dealt with by the Pengadian Niaga there will be coercion on the substance of sharia economic law into conventional economic law, not in sync between the settlement of the dispute with the contract and the concept of solving the case prioritizing business principles and business competition rather than substantive justice. Based on the theory of authority and the principle of the lex specialist, it was found the conclusion that bankruptcy cases and PKPU based on the absolute sharia contract became the absolute competence of the Religious Courts.